Mechanistic Insight into the Copper‐Catalyzed Regiodivergent Silacarboxylation of Allenes with CO2. Issue 15 (13th July 2016) - Yuan, Ruming; Hu, Rong; Fu, Gang
Abstract: DFT calculations were performed to investigate the detailed reaction mechanisms in the copper‐catalyzed regiodivergent silacarboxylation of allenes. According to our calculations, the catalysis would bifurcate at the allene silylcupration step, followed by CO2 insertion, eventually leading to the carboxylated vinylsilane or allylsilane products. The gaps between the two silylcupration barriers were predicted to be −2.3, −0.4, and 2.2 kcal mol −1 when using ( rac )‐Me‐DuPhos, dcpe, and PCy3 (+H2 O) as the ligands, which nicely accounted for the experimental vinylsilane/allylsilane ratios of 93:7, 50:50, and 15:85, respectively. By means of transition‐state‐energy decomposition, we found that the energy penalty of catalyst deformation into its transition‐state geometry was the key factor in determining the direction of the reaction. The switchable regioselectivity by using different P ligands could be ascribed to structural changes of the Cu−Si and Cu−P bonds during the silylcupration process. Abstract : Copper America : DFT calculations were performed to investigate the detailed reaction mechanisms for the copper‐catalyzed regiodivergent silacarboxylation of allenes. Based on these calculations, the catalysis would bifurcate at the allene silylcupration step, followed by CO2 insertion, eventually leading to the carboxylated vinylsilane or allylsilane products.